LEADERSHIP UP THE LADDER: THE CONSTRUCTION OF LEADERSHIP STYLES IN THE HOSPITALITY INDUSTRY - Whitelaw, Paul A. (The journal of contemporary issues in business and government, 2013)
This paper explores and quantifies the differences in the perceptions of leadership styles suitable for various outcomes across three levels of management in the Melbourne hospitality industry. Using a well established self-administered instrument, the Multifactor Leadership Questionnaire (MLQ) v5, the researcher used a ‘snow balling’ technique to recruit a self-selected sample of 282 residents of Melbourne, Australia who work in large, international standard hotels and major catering companies with more than 100 staff. The respondents were classified as working at one of three managerial levels; senior manager, middle manager, or front line manager wherein each level encountered different challenges in the nature of their work and thus required different approaches to leadership. The data indicated that there are several differences within and across the three managerial levels in their leadership styles depending upon the goal at hand. These differences include the specific types of leadership style adopted, and the number of styles adopted, both within and across the task at hand. The author wishes to formally acknowledge the support of MLQ Pty. Ltd. for granting permission to use the MLQ Instrument.